Molecular analyses of the genus Ilex (Aquifoliaceae) in southern South America, evidence from AFLP and its sequence data - Gottlieb, A.M. (2005)
In order to clarify the relationships among southern South American (sSA) representatives of the genus Ilex, an amplified fragment length polymorphism (AFLP) analysis was accomplished. In addition, the phylogenetic relationships of the species were studied using ribosomal internal transcribed spacer (ITS) sequence data alone and in combination with AFLP data, taking into account the possible existence of paralogous sequences and the influence of alignment parameters. To explore stability of phylogenetic hypotheses, a sensitivity analysis was performed using 15 indel-substitution models. Within each species assayed, the AFLPs allowed the recognition of several diagnostic bands. Furthermore, the AFLP analysis revealed that individuals belonging to the same morpho-species formed coherent clades. In addition, some cases of geographical association were noted. Studies on ITS sequences revealed divergence between data obtained herein and sequence data downloaded from GenBank. The sensitivity analyses yielded different interspecific hypotheses of relationships. Notwithstanding, analyses of the ITS data alone and in combination with AFLPs, rendered clades stable to variation in the analytical parameters. Topologies obtained for the AFLPs, the ITS data alone and the combined analyses, demonstrated the existence of a group formed by I. argentina, I. brasiliensis, I. brevicuspis, I. integerrima, and I. theezans, and that I. dumosa and I. paraguariensis were distantly related to the former. Incongruence with traditional taxonomical treatments was found.